New tools for investigating astrocyte-to-neuron communication - Li, Dongdong; Agulhon, Cendra; Schmidt, Elke; Oheim, Martin; Ropert, Nicole (Frontiers in Cellular Neuroscience, 2013)
Grey matter protoplasmic astrocytes extend very thin processes and establish close contacts with synapses. It has been suggested that the release of neuroactive gliotransmitters at the tripartite synapse contributes to information processing. However, the concept of calcium (Ca2+)-dependent gliotransmitter release from astrocytes, and the release mechanisms are being debated. Studying astrocytes in their natural environment is challenging because: i) astrocytes are electrically silent; ii) astrocytes and neurons express an overlapping repertoire of transmembrane receptors; iii) astrocyte processes in contact with synapses are below confocal and two-photon microscope resolution; iv) bulk-loading techniques using fluorescent Ca2+ indicators lack cellular specificity. In this review, we will discuss some limitations of conventional methodologies and highlight the interest of novel tools and approaches for studying gliotransmission. Genetically encoded Ca2+ indicators (GECIs), light-gated channels, and exogenous receptors are being developed to selectively read out and stimulate astrocyte activity. Our review discusses emerging perspectives on: i) the complexity of astrocyte Ca2+ signalling revealed by GECIs; ii) new pharmacogenetic and optogenetic approaches to activate specific Ca2+ signalling pathways in astrocytes; iii) classical and new techniques to monitor vesicle fusion in cultured astrocytes; iv) possible strategies to express specifically reporter genes in astrocytes.